Managing the Orientation Towards Competition in Handball of Students of the Department of Physical Education and Sports Sciences - Abbas, Omar Nouri (Pubmedia Jurnal Pendidikan Olahraga, 2024)
The research aims to identify the management of the orientation towards competition in handball for students of the Department of Physical Education and Sports Sciences and the differences in the management of the orientation towards competition in handball for the students of the Department of Physical Education and Sports Sciences according to the gender variable (males - females). The researcher used the descriptive method because it is suitable for the research procedures. The research community consisted of students from the Department of Physical Education and Sports Sciences, third stage, morning study at Al-Mustansiriya University / College of Basic Education for the academic year (2023 - 2024). The sample consisted of (90) male and female students distributed into three sections, with (65) males and (30) females. The researcher randomly selected a sample of (50) of them, with (25) males and (25). The research tool was the management of orientation toward competition, designed by (Mohamed Hassan Allawi) to measure the management of orientation toward competition for students of physical education and sports sciences because it represents one of the important dimensions of athletic achievement goal orientations. The researcher used the statistical package (SPSS), version (25), to obtain the results. The researcher concluded from the results that there is a case of managing the orientation towards competition among the students of the Department of Physical Education and Sports Sciences, as well as the absence of significant differences in the case of managing the orientation towards competition among the students of the Department of Education and Sports Sciences according to the gender variable (males - females).